2014
DOI: 10.1590/0103-8478cr20140066
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stability of refrigerated fish pates containing loquat seed extract

Abstract: This study investigated the effects of hydroethanolic E. japonica seed extracts (EJSE) as inhibitors of lipid and protein

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…Assim, pode-se sugerir que o tempo de armazenamento dos patês não foi longo o suficiente para que houvesse a produção de compostos secundários da oxidação lipídica, já que os valores de TBARS ficaram bem inferiores a este limite. Fato semelhante foi observado no estudo de Piccolo et al (2014), que investigou os efeitos de extratos hidroetanólicos de semente de Eriobotrya japonica na oxidação lipídica de patês a base de carne de pescado armazenados refrigerados. Os resultados mostraram que nas concentrações testadas, os extratos não foram capazes de inibir ou reduzir as reações de oxidação.…”
Section: Iat 5%unclassified
“…Assim, pode-se sugerir que o tempo de armazenamento dos patês não foi longo o suficiente para que houvesse a produção de compostos secundários da oxidação lipídica, já que os valores de TBARS ficaram bem inferiores a este limite. Fato semelhante foi observado no estudo de Piccolo et al (2014), que investigou os efeitos de extratos hidroetanólicos de semente de Eriobotrya japonica na oxidação lipídica de patês a base de carne de pescado armazenados refrigerados. Os resultados mostraram que nas concentrações testadas, os extratos não foram capazes de inibir ou reduzir as reações de oxidação.…”
Section: Iat 5%unclassified
“…The combination of liquid smoke nanocapsules applied to the catfish fillet was able to inhibit the oxidation of fat. The decreasing of TBA value indicated that the secondary oxidation products formation which not detected with TBA value (Piccolo et al, 2014).…”
Section: Thiobarbituric Acid (Tba) Analysismentioning
confidence: 88%
“…The TBA value of catfish fillet during storage was presented in Figure 3. TBA measured the amount of malonadehid which is the final product of fat oxidation (Piccolo et al, 2014). Based of figure 3, it could be seen that the TBA value of catfish fillet increased until 4 days of storage, for storage of room temperature from 3.53 mg malonaldehid/kg to 4.73 mg malonaldehid/kg.…”
Section: Thiobarbituric Acid (Tba) Analysismentioning
confidence: 95%
“…Devido a sua composição, o pescado, bem como os seus derivados, é um produto bastante susceptível à oxidação lipídica, uma alteração difícil de ser controlada, responsável por sabores e odores indesejáveis, normalmente denominado de ranço (Ferreira et al, 2016, Piccolo et al, 2014. Além de alterações na qualidade sensorial, a oxidação lipídica acarreta destruição de vitaminas lipossolúveis e ácidos graxos essenciais.…”
Section: Determinação De Prazo Comercialunclassified